Pengaruh Komposisi Media Tanam Berupa Campuran Vertisol, Pasir Dan Arang Sekam Terhadap Sifat Fisik Tanah, Pertumbuhan Dan Hasil Lobak - Bako, Peters O; Airtur, Moresi M.; Serangmo, Diana Y. L.; Kapa, Max J.; Kertiawan, Komang (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2022)
An experimental research was carried out on farmer's land in Batuplat Village, Alak District, Kupang City and at the Soil Physics Laboratory, Faculty of Agriculture, Nusa Cendana University. The aims of this study were: (1) to determine the effect of the treatment of the composition of the planting medium in the form of a mixture of vertisol, sand and rice husk charcoal on the physical properties of the soil, growth and yield of rapeseed; and (2) getting the composition of the growing media that gives the best effect on soil physical properties, growth, and radish yield. The study was designed in a single factor experiment using an environmental design in the form of a completely randomized design (CRD). The treatment tested was the composition of the planting medium in the form of a mixture of vertisol, sand and rice husk charcoal, namely: 1 : 1 : 1 (P1); 1 : 1 : 2 (P2); 1 : 2 : 1 (P3); 2 : 1 : 1 (P4); 2 : 2 : 1 (P5) and 2 : 1 : 2 (P6). Each treatment was made in 3 replications so that in total there were 18 experimental units. Parameters observed included: soil bulk density, soil porosity, plant height, number of leaves per plant, and fresh weight of radish tubers. The results showed: (1) the composition of the growing media had a very significant effect on the parameters of fill density and soil porosity, as well as the height and number of leaves per plant at the age of 2 and 4 weeks after planting (MST), but had no significant effect on the fresh weight of radish tubers per plant; (2) there was no treatment of the composition of the planting medium in the form of a mixture of Vertisol, soil, and rice husk charcoal which had the best effect on the physical properties of the soil, growth and yield of rapeseed. Each treatment of the composition of the planting media that was tried was able to change the physical condition of the Vertisols to be better and more conducive to plant growth and development of radish tubers in the soil.